DEVELOPMENT OF MATHEMATICS LEARNING MEDIA ON THE SET MATERIAL BASED ON MACROMEDIA FLASH 8 - Noviana Puspita Permatasari; Abdul Taram (Universitas Ahmad Dahlan, 2018)
Mathematics is a basic science that is very important and beneficial to the development of science and technology. The use of learning media based on Information and Communication Technology (ICT) becomes one a tool alternative for teachers in presenting the subject of mathematics. The set subjects still considered difficult for some students. Learning media based on Macromedia Flash 8 is expected to be facilities that support learning. This research is a development that aims to produce instructional media using Macromedia Flash 8 in learning mathematics on the subject of a set of class VII SMP. This development study using the ADDIE development model that is Analysis, Design, Development, Implementation, Evaluation. Subjects were matter experts, media experts, and junior high SMP Muhammadiyah 5 Yogyakarta and SMP Muhammadiyah 7 Yogyakarta. The instrument used in this study is a questionnaire. The data analysis technique conducted qualitatively and quantitatively to calculate the results of the feasibility test score developed in instructional media. Based on the quality of every aspect of learning media, results of research-based math learning media development of mathematics learning media based on Macromedia Flash 8 is from materials experts with perfect category, an average score is 79,67, from media experts with perfect category, an average score is 105,33, and the response of students with perfect category with an average score of 66,50. Based on the assessments, then the media-based mathematics learning Macromedia Flash 8 is very feasible to use in learning.